The strategic importance of the military attaché in implementing foreign policy (قضايا سياسية, 2024)
Countries always seek to obtain military information about their competitors, where the military attaché is the main source for this goal. Military attachés are posted at embassies and high commissions around the world, and oftentimes, these senior officers are the only visible representation of the armed forces in the countries in which they serve. The more professional the attaché is, the better his observations will be to obtain information and establish relations with the host country. The military attaché plays an effective role in implementing foreign policies in many countries of the world. Public international law does not impose any obligation on states to enter into diplomatic relations, or to send or receive diplomatic envoys, and therefore entering into an agreement and maintaining such relations is the state’s privilege. States are not obligated to send military attaches, nor required to accept them on their territories, yet they will continue to do so, because contemporary international relations, whether in times of peace or war, are inconceivable without appropriate military and security cooperation, in which the military attaché plays a very important role. Therefore, this study will attempt to explain this role of the military attaché and address some of the experiences of two countries, the United States and Canada. The paper examines that selection criterion and training process of the military attaché to support the current diplomatic environment and foreign policies. The study aims to make a general assessment of the role and importance of the military attaché, and is considered a contribution to defense studies on military attaches, at least their activities during their service or the system of military attaches and their role in foreign policy as a basic subject of study, especially with the scarcity of studies in this field.